2013
DOI: 10.1002/fam.2217
|View full text |Cite
|
Sign up to set email alerts
|

The impact of smoke on walking speed

Abstract: SUMMARYIn fire safety engineering, information about the expected walking speed of occupants through smoke is often one factor that is of interest to the designer. However, despite the fact that research already in the 1970s demonstrated that people tend to evacuate through smoke, little research has been performed on the topic since, and evidently, there is a lack of data on walking speed in smoke. This has created a situation where fire safety engineering assessments of the required safe escape time may be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…No data was found on limited ability to sense smoke, although smoke is one of the key signatures that can help to detect a fire [9,39]. The impact of smoke on movement and behaviour has been investigated in the literature [16,17,29,54,60], but no dedicated studies were found. In Table 1, the evacuation activity Smelling emergency cues predominant activity Purposeful sensory experiences is the block assigned, and Other purposeful sensing as category.…”
Section: Resultsmentioning
confidence: 99%
“…No data was found on limited ability to sense smoke, although smoke is one of the key signatures that can help to detect a fire [9,39]. The impact of smoke on movement and behaviour has been investigated in the literature [16,17,29,54,60], but no dedicated studies were found. In Table 1, the evacuation activity Smelling emergency cues predominant activity Purposeful sensory experiences is the block assigned, and Other purposeful sensing as category.…”
Section: Resultsmentioning
confidence: 99%
“…According to Jin [61] it can be expected that movement through smoke will affect the movement time of the occupants; however research conducted by Fridolf et al [62] have quoted that "when the visibility is higher than 2.5 m, it may be argued that visibility does not affect the walking speed". It has therefore been assumed that the occupant walking speed will not be affected before untenable conditions develop, for example visibility less than 10 or 5 m respectively.…”
Section: Movement Phase (Tm)mentioning
confidence: 99%
“…As it is possible to quantify the physical capabilities of people, there are multiple studies over these phenomena, e.g. [61,62], along with mathematical models that use this knowledge for the estimation of the movement of people.…”
Section: Evacuation "(D) Occupants Can Leave the Construction Work mentioning
confidence: 99%